TSUNAMI HAZARD LEVEL MAPPING USING GEOGRAPHIC INFORMATION SYSTEMS IN TRENGGALEK REGENCY - M. Rakif Panguale; Moh. Saiful Rahman Hamka; Syafril Mayu Dinata; Ryzka Arsalia; Aisyah Nur Nabila; Santi Febrianti; N.A.A. Dinda Agustina (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
Indonesia’s southern coastal regions, including Trenggalek Regency, are highly vulnerable to tsunamis due to their proximity to the active subduction zone along the Indian Ocean. Accurate hazard mapping is therefore crucial to support disaster risk reduction efforts. This study aims to analyze and map the tsunami hazard level in the coastal region of Trenggalek Regency using a spatial modeling approach based on Geographic Information Systems (GIS). The method integrates topographic slope, surface roughness, and tsunami wave height data to estimate inundation extent through a mathematical model that incorporates Hloss (wave height loss). The model outputs were used to generate a tsunami hazard index, ranging from 0 to 1, and classified into three hazard classes: low, medium, and high. The results indicate that coastal areas with flat terrain and low roughness coefficients such as settlements and rice fields in the districts of Watulimo, Panggul, and Munjungan are categorized as high hazard zones due to their vulnerability to wide-scale inundation. In contrast, forested or steep-sloped regions demonstrate limited inundation extents due to greater physical resistance. This spatial mapping provides essential information for disaster mitigation, coastal planning, and early warning system development in tsunami-prone areas.